2018
DOI: 10.5194/acp-2018-692
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fine dust emissions from active sands at coastal Oceano Dunes, California

Abstract: Abstract. Sand dunes and other active sands generally have a low content of fine grains and, therefore, are not considered to be major dust sources in climate models. However, recent remote sensing studies have indicated that a surprisingly large fraction of dust storms are generated from regions covered by sand dunes, leading these studies to propose that sand dunes might be globally-relevant sources of dust. To help understand the dust emission potential of sand dunes and other active 15 sands, we present in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 96 publications
1
12
2
Order By: Relevance
“…However, while Marticorena et al [58] and Laurent et al [59] assigned dune fields with fine and coarse sands, we chose to use silty medium sands (SMS), a mixture of fine and coarse sands and silts as sediment structure for dune fields and sand sheets. This integrates the findings of Baddock et al [17], Crouvi et al [48] and Huang et al [49], who assumed that dune fields must include coatings or aggregates of finer particles that can break down into smaller particles to explain the dust activity of dunes. For the class of highly emissive alluvial sediments, a surface sediment structure consisting of 100% of silt particles was chosen to support the high dust activity from these sources.…”
Section: Determination Of Soil Parameterssupporting
confidence: 85%
See 2 more Smart Citations
“…However, while Marticorena et al [58] and Laurent et al [59] assigned dune fields with fine and coarse sands, we chose to use silty medium sands (SMS), a mixture of fine and coarse sands and silts as sediment structure for dune fields and sand sheets. This integrates the findings of Baddock et al [17], Crouvi et al [48] and Huang et al [49], who assumed that dune fields must include coatings or aggregates of finer particles that can break down into smaller particles to explain the dust activity of dunes. For the class of highly emissive alluvial sediments, a surface sediment structure consisting of 100% of silt particles was chosen to support the high dust activity from these sources.…”
Section: Determination Of Soil Parameterssupporting
confidence: 85%
“…To simulate the dust emission flux, sediment supply information was extracted from the four preprocessed Sentinel-2 images. To reduce the complexity of the surface, we focused on two dominant dust source types frequently discussed in the literature, i.e., the alluvial sediments (e.g., [1,14,17,23,26,47]), also discussed in the Introduction, and sand dunes and sand sheets that are receiving increasing attention in recent years [17,48,49]. The following sections describe the strategies for the extraction of these surfaces from the optical remote sensing data and their combination into a sediment supply map (SSM), which is directly included in the dust-emission modeling approach.…”
Section: Sediment Supply Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all the abovementioned studies have been carried out in artificial conditions of glass “test‐tube” chambers that do not simulate natural aeolian processes of saltating sand particles (Bullard et al, 2004, 2007; Kuenen, 1960; Smith et al, 1991; Whalley et al, 1982, 1987; Wright et al, 1998). Recent aeolian simulations in a boundary layer wind tunnel and field measurements have suggested that aeolian abrasion produces only a minor contribution to dust generation from active sands (Huang et al, 2019; Swet et al, 2019). Both studies show that the removal of clay coatings from the surface of quartz and feldspar sands is a dominant mechanism of dust emission.…”
Section: Introductionmentioning
confidence: 99%
“…(2020) identified that studies have described PSD of dust at source at height zero (emission‐dust PSD), PSD of dust suspended in the air (airborne‐dust PSD), and dust emission‐flux PSD that is predicted by dust emission models. Conditions of previous studies include wind tunnel experiments (Alfaro et al., 1997; Gillette et al., 1974) and field measurements from bare agricultural fields or other largely unvegetated landscapes with the near‐unlimited supply of LEM, and fetch sufficient for transport‐limited equilibrium saltation (e.g., Fratini et al., 2007; Gillette et al., 1972; Gillies & Berkofsky, 2004; Huang et al., 2019; Shao, Ishizuka, et al., 2011; Sow et al., 2009; Zobeck & Van Pelt, 2006). Some measurements under near‐idealized conditions indicate there is no statistically significant dependence of emission‐flux PSD on u * (Kok, 2011).…”
Section: Introductionmentioning
confidence: 99%